On the rise of health spending and longevity - Raquel Fonseca; Pierre-Carl Michaud; Titus Galama; Arie Kapteyn (Institute for the Study of Labor (IZA), 2009)
We use a calibrated stochastic life-cycle model of endogenous health spending, asset accumulation and retirement to investigate the causes behind the increase in health spending and life expectancy over the period 1965-2005. We estimate that technological change along with the increase in the generosity of health insurance may explain independently 53% of the rise in health spending (insurance 29% and technology 24%) while income less than 10%. By simultaneously occurring over this period, these changes may have lead to a synergy or interaction effect which helps explain an additional 37% increase in health spending. We estimate that technological change, taking the form of increased productivity at an annual rate of 1.8%, explains 59% of the rise in life expectancy at age 50 over this period while insurance and income explain less than 10%.
Keywords: I10; I38; J26; 330; Demand for health; health spending; insurance; technological change; longevity; Gesundheitsversorgung; Nachfrage; Gesundheitskosten; Gesetzliche Krankenversicherung; Medizin; Technischer Fortschritt; Sterblichkeit; Einkommen; Schätzung; USA